Mapping The Journey Path For Sustainable Innovation: How A Start-up Pursues Growth Through Leveraging Dynamic Capabilities - Anjar Priyono; Siti Nurulhuda Nordin; Tri Lestari Wahyuning Utami; Norasikin Hj Salikin; Mahdhir Abdullah; Sumaiyah Abd Aziz (Springer Nature Link, 2025)
Indexed by WOS